A BAHD acyltransferase contributes to the biosynthesis of both ethyl benzoate and methyl benzoate in the flowers of Lilium oriental hybrid ‘Siberia’ - Yue, Yuechong; Wang, Lan; Li, Manyi; Liu, Fang; Yin, Junle; Huang, Lijun; Zhou, Bin; Li, Xinyue; Yu, Yunyi; Chen, Feng; Yu, Rangcai; Fan, Yanping (Frontiers in Plant Science, 2023)
Lily is a popular flower worldwide due to its elegant appearance and pleasant fragrance. Floral volatiles of lily are predominated by monoterpenes and benzenoids.While a number of genes for monoterpene biosynthesis have been characterized, the molecular mechanism underlying floral benzenoid formation in lily remains unclear.Here, we report on the identification and characterization of a novel BAHD acyltransferase gene that contributes to the biosynthesis of two related floral scent benzoate esters, ethyl benzoate and methyl benzoate, in the scented Lilium oriental hybrid 'Siberia'. The emission of both methyl benzoate and ethyl benzoate in L.'Siberia' was found to be tepal-specific, floral development-regulated and rhythmic.Through transcriptome profiling and bioinformatic analysis, a BAHD acyltransferase gene designated LoAAT1 was identified as the top candidate gene for the production of ethyl benzoate. In vitro enzyme assays and substrate feeding assays provide substantial evidence that LoAAT1 is responsible for the biosynthesis of ethyl benzoate.It was interesting to note that in in vitro enzyme assay, LoAAT1 can also catalyze the formation of methyl benzoate, which is typically formed by the action of benzoic acid methyltransferase (BAMT). The lack of an expressed putative BAMT gene in the flower transcriptome of L. 'Siberia', together with biochemical and expression evidence, led us to conclude that LoAAT1 is also responsible for, or at least contributes to, the biosynthesis of the floral scent compound methyl benzoate. This is the first report that a member of the plant BAHD acyltransferase family contributes to the production of both ethyl benzoate and methyl benzoate, presenting a new mechanism for the biosynthesis of benzoate esters.